MCMC based modelling of queuing systems from empirical data - Landauskas, Mantas; Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2011)
Markov chain Monte Carlo (MCMC) modelling technique requires one to be able to construct a proposal density. There is no universal way to achieve this. This paper considers the universal proposal selection technique based on the kernel density estimate. Two channel queuing system with a priority was modelled using this technique. Empirical data (the observed service times) and the rates of arrival processes are all the information used for simulating the system.